Analysis of the Linkages between Foreign Investment, Trade, and Economic Structure on Tax Revenue in Asia - Utama, Muhammad Budi; Harianto, Tedi (Business Management, 2025)
Tax revenue is the main source of funding in various countries, including countries in Asia. However, in the Asian context, there are still some serious problems related to tax revenue, such as tax ratio problems and tax evasion. This study identifies the determinants of tax revenue in Asia over the period 2008-2023. We use the Generalized Method of Moments (GMM) model to analyze the results and find that foreign investment inflows and per capita GDP increase are the main sources of tax revenue increase compared to agriculture, manufacturing, and trade. For this reason, the government is expected to review the tax policies that have been issued to achieve a balance in state tax revenue.